FREEDOM & IMPARTIAL OF JUDICIARY : ANTARA “ PERADILAN BEBAS” & “PERS YANG BEBAS - Indriyanto Seno Adji (Jurnal Hukum dan Peradilan, 2015)
Press of independence adopted by Law No. 40 of 1999 on the Press is an accentuation of the Libertarian Press system which requires the existence of a absolute total "freedom of pers" by putting all the legal consequences on the substance of its news through judicial institutions, without calls for criminalization forms of the press with all the reason and limitedly direction purpose. Absolute Privilege Right of the Press have signs that provide a limitation on -moral hazard- based on Interest of justice or national security or for the prevention of disorder or crime that can be issued by the judiciary as a form of Sub Judice Rule criteria or Disobeying a Court Order from Contempt of Court institutions. a proclamation which is a form of freedom of expression with the news that "prejudicial", even the news substance pose a "misleading conclusion and opinion" as well as has provided an opinion and conclusions that are misleading or incorrect and negative impact on the course of judicial proceedings and other parties broadly (as recognition of the Press Libertarian System) may be faced with a sense of responsibility of the press itself, either ethic norms and laws.Keywords : Judicial, Pers, Freedom